Technological factors and e-commerce adoption among small medium enterprises in Kurdistan, Iraq - Abduljabbar Sultan, Abdulsatar; Muhamad Noor, Sarina; Nasirun, Noraini (International Journal of Engineering and Technology, 2018)
The adoption of e-commerce among SMEs plays an important role in the development of economy in a particular country. However, previous studies found the inconsistency results, especially between the developed and developing countries. Thus, there is the need for more studies to be conducted in order to get the insight of this research area. Therefore, the aim of this study is to identify the technological factors influencing the e-commerce adoption among SMEs in Kurdistan, Iraq. Data were collected among SMEs in Kurdistan area namely Erbil, Sulaymaniyah and Duhok. 200 SMEs participated in this study. The results exhibit that relative advantage and compatibility have significant influence to e-commerce adoption in Kurdistan, Iraq. The main contribution of this study is discussed at the end of the article.Â Â